Surface oxygen effect on the selective oxidation of benzyl alcohol over Mn/C & V/C catalysts - Chen, Wan. (2009)
The aerobic selective oxidation of benzyl alcohol on manganese and vanadium catalysts supported on activated carbon (Mn/C and V/C) pretreated in liquid or gas phase oxidation has been investigated. Significant improvement of the catalytic activity was observed when pretreatments of the carbon support are carried out through three oxidation routes for both types of the catalysts. Characterizations of nitrogen physisorption and X-ray absorption were involved to identify the catalyst surface properties. Evidences were found that all the Mn/C catalysts correspond to a local coordination of Mn as that in Mn3O4, whereas all V/C catalysts have distorted tetrahedral local coordination and valence of 5+ for vanadium atoms. By eliminating the effect of the nature of catalytic species and surface area, the catalytic activity was proposed to be correlated with the catalyst surface oxygen density.